Pengembangan bahan ajar teks fabel bermuatan nilai peduli dengan pendekatan saintifik pada MTS Miftahul Khair - Jubaidah, Jubaidah; Soe'oed, Rahmat; Siddik, M. (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The purpose of this research is to identify the development process, measure effectiveness, and evaluate the appeal of instructional materials in the form of value-based fable texts using a scientific approach for students in the seventh grade of Madrasah Tsanawiyah Miftahul Khair Loa Janan, Kutai Kartanegara Regency. This research employs the research and development (R&D) method. The research resulted in a module of value-based fable texts with a scientific approach for seventh-grade students, which is overall excellent and aligned with the 2013 curriculum. Expert assessments from subject matter experts, instructional design experts, students, and subject teachers indicate that the module has a clear content presentation, an attractive layout, good readability, and significant benefits in enhancing students' competence. The development of this instructional material has proven to be effective, as evidenced by improved student learning outcomes after using the module. Although some students initially did not reach the minimum passing grade, the post-test results showed significant improvement, influenced by both teacher and student factors. In conclusion, this module has successfully created effective instructional materials to enhance students' competence in writing value-based fable texts using a scientific approach.